Millions of microplastics released from a biodegradable polymer during biodegradation/enzymatic hydrolysis. (1st March 2022) - Wei, Xin-Feng; Capezza, Antonio J.; Cui, Yuxiao; Li, Lengwan; Hakonen, Aron; Liu, Baicang; Hedenqvist, Mikael S.
Highlights: Large amout of microplastics from biodegradable polyester were formed during enzymatic hydrolysis in aqueous environment. Microplastics showed heavily eroded surfaces. Release of microplastics was due to the uneven surface erosion rate. Hydrolysis products such as acidic monomers and oligomers were also released during the enzymatic hydrolysis process. Abstract: In this article, we show that enzymatic hydrolysis of a biodegradable polyester (poly(ε-caprolactone)) by Amano Lipase PS in an aqueous (buffer) environment yielded rapidly an excessive number of microplastic particles; merely 0.1 g of poly(ε-caprolactone) film was demonstrated to yield millions of particles. There were also indications of non-enzymatic hydrolysis at the same conditions, but this did not yield any particles within the time frame of the experiment (up to 6 days). Microplastic particles formed had irregular shapes with an average size of around 10 µm, with only a few reaching 60 µm. The formation of microplastic particles resulted from the uneven hydrolysis/erosion rate across the polymer film surface, which led to a rough and undulating surface with ridge, branch, and rod-shaped micro-protruding structures. The consequent detachment and fragmentation of these micro-sized protruding structures resulted in the release of microplastics to the surroundings. Together with microplastics, hydrolysis products such as acidic monomers and oligomers were also released during the enzymatic hydrolysis process, causing a pH decrease in the surrounding liquid. The results suggest that the risk of microplastic pollution from biodegradable plastics is notable despite their biodegradation. Special attention needs to be paid when using and disposing of biodegradable plastics, considering the enormous impact of the paradigm shift towards more biodegradable products on the environment. Graphical abstracts: Image, graphical abstract